Immigration status and cervical test screening: more underscreening and inequality social health. (13th November 2019) - Sassenou, J; Rigal, L; Ringa, V
Abstract: Introduction: In France, public health authorities recommend cervical cancer screening (CCS) by a Pap test every 3 years for all sexually active women aged 25 to 65 years. Socioeconomic inequalities are observed in CCS and disparities in screening practices according to immigration status has been reported. The aim of this study was to compare income inequalities in cervical screening depending on immigration status. Methods: The study was based on the 2012-2016 baseline data in the Constances cohort (N = 28905 women). Delayed CCS was defined by having last CCS for more 3 years. The main independant variables were monthly household income and immigration status. The women's origin was divided into the following categories: French women born to two French parents (French origin), French women born to at least one foreign parent (immigrant origin), and women born to two foreign parent (immigrants). Immigrants were divided into two categories: women with French or not nationality (naturalized or foreign immigrant). The slope index inequality (SII) was computed to measure the income inequality in CCS non-adherence. Interaction test was used to compare SII depending on immigration status. We used imputation model. Results: We confirmed the existence of a gradient with respect to migration origin for delaying CCS (21, 9 % women of French origin, 26, 5 % women of immigrant origin, 28, 8 % immigrant, p < 10-4). More income inequalities were observed depending on immigration status (SII French origin= 0, 17 [0, 16-0, 18], SII immigrant origin= 0, 28 [0, 24-0, 32], SII immigrant = 0, 27 [0, 25-0, 31], p interaction <0, 001). Among immigrant women, we observed difference in social inequalities depending on French nationality (SII naturalized= 0, 19 [0, 15-0, 23], SII foreign immigrant= 0, 35 [0, 30-0, 40], p interaction <10-4). Conclusions: French women of immigrant origin and immigrant women are underscreened and social inequalities are stronger among them than French women of French origin. Key messages: French women of immigrant origin and immigrant women are less detected for cervical cancer screening than French women. French women of immigrant origin and immigrant women are detected for cervical cancer screening with more social inequalities than French women of french origin.